"We're in the same book, but we're in different parts of the book": Dominant and sub-group narratives of life following a Down syndrome determination. (March 2023) - Sangster, Sarah L.; DeLucry, Kailey J.; Lawson, Karen L.
Parents of children with Down syndrome (DS) were interviewed about if their experiences raising their children matched their initial assumptions about parenting a child with DS. A dominant narrative was identified, wherein most parents described initially having negative assumptions, which did not come to fruition; parenting their child was not very different from parenting a typical child. There was also a sub-group of participants who disputed the dominant narrative; parenting their child was challenging and the dominant narrative marginalizes that experience. The findings indicate that although for many parents, having a child with DS is like " taking the scenic route " (i.e., it involves a few more hurdles, but often more rewards), this framing is not always applicable. Therefore, health care providers and support organizations should promote a narrative that encompasses the diversity of parenting a child with DS.